MODELS OF STATE ECONOMIC AND FINANCE POLICY IN THE FIELD OF ECONOMY DIVERSIFICATION - Sergey A. Balandin (Вестник Российского экономического университета имени Г. В. Плеханова)
The article describes approaches to the impact of state economic policy on the industrial sphere in the process of economy diversification, which are used in global practice. The author identifies three groups of countries (the EU, the US, Asian-Pacific countries) and for each of them he defines key peculiarities of economic policy from the point of view of economy diversification . On the basis of these countries' experience three models of economic policy in economy diversification were analyzed: European, American, Asian-Pacific. For each of these models key specific features allowing us to characterize the process of designing policy diversification were demonstrated. Concrete directions of state economic policy aiming at national economy diversification were identified.